2014
DOI: 10.1186/1743-422x-11-101
|View full text |Cite
|
Sign up to set email alerts
|

A description of the hepatitis B virus genomic background in a high-prevalence area in China

Abstract: BackgroundHepatitis B (HB) is an important disease worldwide. Almost 350 million people are positive for Hepatitis B virus surface antigen (HBsAg), and one-third of them live in China. According to a nation-wide serosurvey in China in 2006, the prevalence of HBsAg was higher in Northwest China than in other areas. However, the epidemic HBV strains in this area are poorly studied.ResultsIn this study, 242 complete hepatitis B virus (HBV) genome sequences were obtained from HBV asymptomatic carriers in major cit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
2
4
1
Order By: Relevance
“…The three most prevalent serotypes were adr (36%), adw2 (29%) and ayw1 (19.9%). We found serotypes adr, ayr and ayw3 most commonly associated with genotype C, adw2 for B and C, adw3 and ayw1 for B, and ayw2 for D. These findings differ to Norder's study [13], which reported that the serotypes adw2, ayw1 and ayw3 were more pronounced amongst genotypes A, B and D. Moreover, our observations of HBsAg subtype distribution for genotypes B and D are dissimilar to the finding of Chen et al [71] who reported that adr and ayw2 were prevalent among genotype B strains while most of genotype D sequences were assigned to adr [71]. This is likely due to the geographical selection of HBV sequences used in this study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The three most prevalent serotypes were adr (36%), adw2 (29%) and ayw1 (19.9%). We found serotypes adr, ayr and ayw3 most commonly associated with genotype C, adw2 for B and C, adw3 and ayw1 for B, and ayw2 for D. These findings differ to Norder's study [13], which reported that the serotypes adw2, ayw1 and ayw3 were more pronounced amongst genotypes A, B and D. Moreover, our observations of HBsAg subtype distribution for genotypes B and D are dissimilar to the finding of Chen et al [71] who reported that adr and ayw2 were prevalent among genotype B strains while most of genotype D sequences were assigned to adr [71]. This is likely due to the geographical selection of HBV sequences used in this study.…”
Section: Discussioncontrasting
confidence: 99%
“…This is likely due to the geographical selection of HBV sequences used in this study. We targeted Southeast Asia, Australia and New Zealand, while the Norder study [13] was worldwide and the Chen study [71] focused on China.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the HBV genotype profile identified in the overt HBV infection in Northwest China, the dominant genotype isolated from OBI cases was genotype D (77.5 %, 62/80), followed by genotype C (21.25%, 17/80) and genotype B (1.25%, 1/80). These results suggest that the genotype composition of OBI was the same as the overt HBV infection in this region.…”
Section: Discussionsupporting
confidence: 61%
“…Moreover, our results highlight that identification of the genotype-dependent sites would be important for the distinction between mutations and mere polymorphisms during mutation analysis, for example, glutamine at rt238 as a low-frequency AA residue in our study was more likely to be a naturally occurring mutation rather than a polymorphism site. In addition, the standard for differentiating genotypes by our genotype-dependent sites analysis may [23,24]. How HBV genotypes potentially modulate NAs resistant mutation still remains controversial [14,25,26].…”
Section: Discussionmentioning
confidence: 99%